β2-microglobulin triggers NLRP3 inflammasome activation in tumor-associated macrophages to promote multiple myeloma progression - Hofbauer, Daniel; Mougiakakos, Dimitrios; Broggini, Luca; Zaiss, Mario; Büttner-Herold, Maike; Bach, Christian; Spriewald, Bernd; Neumann, Frank; Bisht, Savita; Nolting, Jens; Zeiser, Robert; Hamarsheh, Shaima'a; et al. (Immunity, 2021)
As substantial constituents of the multiple myeloma (MM) microenvironment, pro-inflammatory macrophages have emerged as key promoters of disease progression, bone destruction, and immune impairment. We identify beta-2-microglobulin (β2m) as a driver in initiating inflammation in myeloma-associated macrophages (MAMs). Lysosomal accumulation of phagocytosed β2m promotes β2m amyloid aggregation in MAMs, resulting in lysosomal rupture and ultimately production of active interleukin-1β (IL-1β) and IL-18. This process depends on activation of the NLRP3 inflammasome after β2m accumulation, as macrophages from NLRP3-deficient mice lack efficient β2m-induced IL-1β production. Moreover, depletion or silencing of β2m in MM cells abrogates inflammasome activation in a murine MM model. Finally, we demonstrate that disruption of NLRP3 or IL-18 diminishes tumor growth and osteolytic bone destruction normally promoted by β2m-induced inflammasome signaling. Our results provide mechanistic evidence for β2m's role as an NLRP3 inflammasome activator during MM pathogenesis. Moreover, inhibition of NLRP3 represents a potential therapeutic approach in MM.
CRIS-Team Scopus Importer:2021-08-13
Keywords: inflammation; macrophages; multiple myeloma; NLRP3; phagocytosis; tumor-associated macrophages